Effects of purified diets containing different combinations of arachidonic and docosahexaenoic acid on survival, growth and fatty acid composition of juvenile turbot (Scophthalmus maximus) - Castell, John D; Bell, J Gordon; Tocher, Douglas R; Sargent, John R (Aquaculture, 1994)
The objective of this study was to determine the relative essential fatty acid (EFA) growth-promoting activities of pure arachidonic (AA, 20:4n−6) and docosahexaenoic (DHA, 22:6n−3) acids and various concentrations of these two acids in the diet of juvenile turbot (Scophthalmus maximus). Casein-based, semi-purified diets containing 15% fish oil or 14% hydrogenated coconut oil/oleic acid (1:1) supplemented with 1% 20:4n−6, 1% 22:6n−3 or 1% of various combinations of these two acids were fed to duplicate groups of 26 juvenile turbot for 11 weeks. In this trial, feeding the diet containing 20:4n−6 as the only highly unsaturated fatty acid (HUFA) resulted in higher growth and survival than any of the mixtures of the two fatty acids or 22:6n−3 alone. The diet containing 22:6n−3 as the sole HUFA resulted in the lowest growth and survival of all dietary treatments. The control diet with 15% fish oil resulted in a greater growth rate than any of the pure HUFA-supplemented diets. There was a significant effect of dietary lipid on the somatic index of the brain but not heart, kidney or liver. The percentage of lipid in the liver, but not of heart, brain, eyes, gills or kidney, was influenced by dietary lipid, with the highest percentage in fish supplemented with DHA alone. After 11 weeks, the 20:4n−6 and 22:6n−3 levels in whole-body total lipids were strongly influenced by the content of these fatty acids in the diets. The relative effect of dietary levels of these two fatty acids on their content in fish lipids varied considerably among the various organs and tissues of the fish that were analyzed. Brain and eye lipids were generally highest in 22:6n−3 while gill and kidney lipids were consistently higher in 20:4n−6 than the other organs analyzed. The effect of dietary 20:4n−6 on the content of that HUFA in organ lipid was greatest in gill and liver. The greatest impact of dietary 22:6n−3 level on content of that acid in organ lipid was seen in gill and kidney. There were also significant effects of dietary HUFA content ...